Platform proposal impact in the development of some special physical abilities in the level of achievement of ran (1500) meters of the young players in athletics. - Husein, Maysaa (Journal of Physical Education, 2012)
The research included five parts, in 1st part, the researcher mentioned of the importance of research, presentation of the problem, and installs the objectives, mentioned, Hypothesis and areas of research. 2nd part has included theoretical studies which were in regard to the subject. 3rd part, the researcher dealt with the research methodology and procedures, the research method was experimentation–one group, then they across the research sample with details and the method chosen, then they mention to equipments and the tools which used to research and measurements of physical and the test which installed by herself and referred also to the How the adoption of physical abilities in question and choose the tests to measure these abilities, at the end of this part the researcher mention the means of statistical which used in the search. Part 4th the researcher offered from the results obtained through them and they analyzed and discussed these results. In Part 5th the researcher showing conclusions obtained from the analysis and discussion of results and finally the researcher mention some of the recommendations that came on regarding what the researcher concluded.